The Effectiveness of Tax Audit as a Self Assessment System Supervision Measures and Tax Revenue Support (Study at the Large Tax Office 4) - Dian Wahyudin; Indriani Rahayuning Tyas; Anwar Atmojo; Iin Andrayanti; Faizah Julina (Yayasan Ilomata, 2022)
The level of formal taxpayer compliance is still not satisfactory if it is associated with the self-assessment system because there are still quite high gaps. For this reason, it is necessary to carry out a tax audit as a supervisory measure. Through the audit, it is hoped that it will increase the awareness of taxpayers to fulfil their tax obligations and increase tax revenues. This study uses a descriptive qualitative approach with the type of case study. The author uses a target approach, a source approach and a process approach to analyse the effectiveness of tax audits as an act of supervising the self-assessment system and supporting tax revenue. The results of the study indicate that the tax audit is quite effective as an act of monitoring the self-assessment system. This is evidenced by a change in the behaviour of the taxpayers who have been audited. However, it is not effective enough to support tax revenue. The inhibiting factors include the amount of data that must be processed and analysed, facilities and infrastructure with limited capabilities. Efforts have been made to provide infrastructure, especially computers, which can process and analyse large amounts of data quickly, optimize data from internal parties and anticipate field inspections using zoom and being more selective.